The Special Status of Papua in the New Format of Special Autonomy and the Concept of Regional Autonomy in the Perspective of Islamic Law - Bauw, Lily (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This article examines the concept of Papua's specialness in the context of special autonomy, focusing on changes in format and its implementation in Papua Province. This study aims to analyze the implementation of the new format of special autonomy within the national legal framework and assess the conformity of the new format of special autonomy with the principles of Islamic law. Through the normative legal method, this article explores the legal aspects of Papua's special autonomy, including the authority given to the regional government, institutions, finances, including the rights of the Papuan people. This study uses primary and secondary legal sources, including laws and regulations, the Qur'an, Hadith, fatwas, and the views of scholars on regional autonomy in the context of Islam. And data is collected through documents and interviews. The findings of this study indicate that Papua's special autonomy provides space for regional governments in Papua Province to determine policies that are more in line with the needs of the community, but its implementation is still not optimal. From the perspective of Islamic Law, the concept of regional autonomy based on the principles of independence and justice is in line with special autonomy, namely in the management of power based on the principles of deliberation, avoiding exploitation, and maintaining the welfare of the people. The conclusion of this study is important to integrate the principles of Islamic Law within the framework of regional autonomy, in order to create a government that is more just, transparent, and in accordance with the religious and social values ​​that exist in society.